Embedded Simple Excited Automotive Alternator Modeling using Magnetic Equivalent Circuits - Moufida Klach; Helmi Aloui; Rafik Neji; Mohamed Gabsi; Michel Lecrivain (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper presents the modeling by Magnetic Equivalent Circuit model (MEC) of a Simple Excited Automotive Alternator (SE2A) where DC-excitation winding is transferred from rotor side to statorone rather than in conventional automotive claw pole alternators, to overcome the disadvantages of the ring-brush system. Following the resolution of the MEC using Newthon-Raphson numerical method, the alternator performances at both no-load and under resistive load regimes is achieved considering the saturation effect. It has been found that alternator’s performances carried out using the proposed MEC are with closed proximity to experimental records on a built prototype of the considered alternator.